Polaris Battery Labs : startup risk management - Walker, Russell, 1972- (SAGE Knowledge. Cases., 2018)
Polaris Battery Labs was an Oregon-based startup that provided innovation services to companies in the lithium ion battery industry. Its operating philosophy and expertise in this fast-growing industry enabled it to provide great value to its clients, but as a startup that was seeking growth the company was subject to multiple risks.